PENGELOLAAN SUMBERDAYA IKAN KAKAP MERAH (Lutjanus spp.) DI PERAIRAN UTARA CIREBON, LAUT JAWA - Usman, Arif; Sumadhiharga, Ono K.; Patria, Mufti Patala (Jurnal Teknologi Perikanan dan Kelautan, 2014)
Red snapper (Lutjanus spp.) is one of the important commodity of demersal fish at the northern waters of Cirebon, Java Sea. The high degree of traditional fishing operations around the coastal area is expected to affect the availability of the fish stock. The Research results showed that there have been over fishing, it is caused by the large number of traditional fishing vessels at the coastal area, especially the persistence of the fishermen who use unfriendly fishing gear such as mini trawl. And then the red snapper which caught generally is young and never spawn or not yet mature. To solve that problem, it must arrange the amount of fishing vessels which can be operated at coastal area and it must law enforcement, and then to utilize the red snapper resources it advised to use the hook size larger than No. 10 and then install the rumpon at the new fishing ground which wider and farther. So the pressure to fishing ground of snapper can be reduced.